2022
DOI: 10.1016/j.bbih.2022.100425
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in post-ICU patients after severe COVID-19 infection: The role of cognitive reserve

Abstract: Background Cognitive manifestations associated with Severe Acute Respiratory Syndrome by Coronavirus 2 (SARS-CoV-2) are yet to be described in the existing literature. The aim of this exploratory study is to analyze the impact of severe SARS-CoV-2 infection on neuropsychological performance 6 months following hospital discharge, and to identify which medical variables predict worse outcome. In this context, we study if cognitive reserve (CR) may play a protective role on cognitive impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 45 publications
(60 reference statements)
6
36
0
Order By: Relevance
“…Through Kruskal wallish test, we found that patients with COVID-19 infection are indeed related to prognosis anxiety and depression, which will increase the psychological burden. A study found that novel coronavirus pneumonia patients may have some type of cognitive impairment in the long term, especially in the areas of processing speed, verbal memory or executive function 14 . Our study found that novel coronavirus pneumonia is associated with stroke and cognitive impairment also in mild and non severe infection, but not only in severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…Through Kruskal wallish test, we found that patients with COVID-19 infection are indeed related to prognosis anxiety and depression, which will increase the psychological burden. A study found that novel coronavirus pneumonia patients may have some type of cognitive impairment in the long term, especially in the areas of processing speed, verbal memory or executive function 14 . Our study found that novel coronavirus pneumonia is associated with stroke and cognitive impairment also in mild and non severe infection, but not only in severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic activation of the extended autonomic system, including the neuroendocrine and neuroimmune systems, would be associated with an increased risk of developing Long-COVID [ 29 , 89 ]. As mentioned before, SARS-CoV-2 could reach the hypothalamus and activate brain mast cells and microglia to release pro-inflammatory molecules [ 3 , 10 ]. In turn, the autonomic alteration of hypothalamus function may determine cognitive abnormality, sleep dysregulation, and profound fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Long-COVID syndrome consists of many persistent symptoms following COVID-19 illness, which can endure for several weeks or months [ 1 ]. It is estimated to affect at least one-third of patients, with a prevalence increasing in patients hospitalized because of COVID-19 infection [ 2 , 3 ]. One of the most frequent Long-COVID effects is brain fog [ 4 ], a colloquial expression indicating a phenomenon whose clinical impact may be detrimental to an individual’s psychological, occupational, and social life.…”
Section: Introductionmentioning
confidence: 99%
“…Still, data so far do not suggest that post-COVID-19 is explained by persisting central nervous system infection [ 45 ], leaving brain imaging alterations observed largely unexplained [ 53 ]. Other possible aspects may include immune-mediated [ 48 , 54 ], neurodegenerative, hypoxia-related [ 55 , 56 ] or metabolic changes related [ 45 , 57 ] causes. Furthermore we should not neglect possible complex multifactorial explanations including psychiatric network perspectives [ 49 ].…”
Section: Discussionmentioning
confidence: 99%